The effects of combat-related mild traumatic brain injury (mTBI): Does blast mTBI history matter?. Issue 4 (October 2015) - Kontos, Anthony P.; Elbin, RJ; Kotwal, Russ S.; Lutz, Robert H.; Kane, Shawn; Benson, Peter J.; Forsten, Robert D.; Collins, Michael W.
Abstract : BACKGROUND: The effects of mild traumatic brain injury (mTBI) have received significant attention since the beginning of the conflicts in Afghanistan and Iraq. Surprisingly, little is known about the temporal nature of neurocognitive impairment, mTBI, and posttraumatic stress (PTS) symptoms following combat-related mTBI. It is also unclear as to the role that blast exposure history has on mTBI and PTS impairments and symptoms. The purposes of this study were to examine prospectively the effects of mTBI on neurocognitive performance as well as mTBI and PTS symptoms among US Army Special Operations Command personnel and to study the influence of history of blast mTBI on these effects. METHODS: Eighty US Army Special Operations Command personnel with (n = 19) and without (n = 61) a history of blast-related mTBI completed the military version of the Immediate Post-concussion Assessment Cognitive Test (ImPACT), Post Concussion Symptom Scale (PCSS), and the PTSD Checklist (PCL) at baseline as well as 1 day to 7 days and 8 days to 20 days following a combat-related mTBI. RESULTS: Results indicated that verbal memory ( p = 0.002) and processing speed ( p = 0.003) scores were significantly lower and mTBI symptoms ( p = 0.001) were significantly higher at 1 day to 7 days after injury compared with both baseline and 8 days to 20 days after injury. PTS remained stable across the three periods. Participants with a history of blast mTBI demonstrated lower verbal memory at 1 day to 7 days after mTBI compared with participants without a history of blast mTBI ( p = 0.02). CONCLUSION: Decreases in neurocognitive performance and increased mTBI symptoms are evident in the first 1 day to 7 days following combat-related mTBI, and a history of blast-related mTBI may influence these effects. LEVEL OF EVIDENCE: Epidemiologic/prognostic study, level II.